METODE AUDIO-LINGUAL DALAM PEMBELAJARAN KAIWA - Yani, Damai (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2016)
AUDIO-LINGUAL METHOD IN TEACHING KAIWAJapanese is one of the foreign languages studied in Indonesia nowadays. As a means of communication, one of the the most important skill is speaking or conversation skill or kaiwa in Japanese. This paper aims at describing the audio-lingual method in teaching kaiwa for the first year of Japanese language students. The audio-lingual method emphasizes on repetition. It is done for time efficiency in learning a language. The mimicry-memorize technique is used in the implementation of the audio-lingual method in learning kaiwa. The students are promoted to kaiwa and are asked to memorize it. After memorizing it, they are later asked to practice. This technique requires them to be actively involved especially in speaking despite of their fear. Keywords: audio-lingual, kaiwa , mimicry-memoize, percakapan